PENAFSIRAN KONTEKSTUAL ABDULLAH SAEED : (Metodologi dan Aplikasi pada Ayat Jilbab) - M. Zia Al-Ayyubi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2023)
This paper discusses the study of Abdullah Saeed's contextual interpretation by using a philosophical-contextual approach. Departing from the two major camps in understanding the Qur'an, namely the textualist and contextualist camps, this paper is present to discuss how Abdullah Saeed's views, methodology, and application of contextual interpretation. Abdullah Saeed's thinking on the idea of the contextual approach that he offers is the result of the influence of his predecessor, Fazlur Rahman with his double movement idea. In the contextual approach offered by Saeed, he offers the idea of a hierarchy of values as a development and refinement of the idea of moral ideals brought by Fazlur Rahman. The conclusion obtained in this paper is that QS. al-Ahzab/33: 59 has an implementational value, this value changes in its meaning. So, the contextual reading of the concept of covering the aurat (nakedness) by extending the hijab to the chest is not something absolute and definite, in the sense that the need to be stretched out to cover the chest in practice will vary depending on the surrounding context.